Relação pessoa-a-pessoa no pré-natal de alto risco: estudo de caso - Souza, Bruna Felisberto de (Universidade Federal de São Carlos, 2022)
Pregnancy is a physiological phenomenon and, therefore, its evolution occurs without complications in most pregnant women. However, there is a group of women who, based on conditions such as some individual characteristics, sociodemographic conditions, previous reproductive history, clinical conditions prior to pregnancy, may indicate a higher risk of developing pathologies with a potential for unfavorable outcomes. This group of women is called high-risk pregnant women. When diagnosed, they are indicated for concomitant follow-up in high-risk prenatal services. Being in the situation of a high-risk pregnant woman tends to converge the woman and her family towards a fragmented biomedical assistance approach, which gives little value to subjective, emotional, and relational aspects. This exclusively technical and biomedical approach misses the chances of weaving care in its broadest sense, excluding singularities and preventing the establishment of a person-to-person relationship. The general objective of this study was to analyze prenatal care for high-risk pregnant women developed by nurses on home visits based on Joyce Travelbee's nursing theory. The specific objectives were to discuss aspects of the visiting nurse's relationship with the high-risk pregnant women towards autonomy and discuss the incorporation of home visitation by nurses in high-risk prenatal care. A qualitative, field study was proposed, with an interventionist character, under the methodological strategy of the case study. The case was the relationship between nurse and high-risk pregnant woman in the home visit and care. The development of the home visits took place from March 2018 to March 2020, in a city in the interior of São Paulo, when 17 women and high-risk pregnant women were visited by nurses every two weeks. To study and report the cases, the full transcription of the audio recordings of the home visits developed and of the field notes of the visiting and researcher nurses was carried out. The seventeen cases are presented individually, with visibility of the phases proposed by Joyce Travelbee and the needs explored in the person-to-person relationship. The analysis of the cases allowed us to identify that the person-to-person relationship was central and essential for the fabric of care, when the attentive, sensitive, and attentive attitude and the appreciation of the relationship supported and enabled the particularities of these high-risk pregnant women to manifest themselves and be welcomed. The meeting of the sense and significance of the situation of being a high-risk pregnant woman and the circumscribed mothering was always, in some way, launched in the relationship and effected a counterpoint to the insufficiencies experienced in high-risk prenatal care, anchored in the biomedical model they had received until then. It is concluded that producing care guided and driven by the person-to-person theory has the potential to transform the scope of prenatal care, with the potential to transform gestational and delivery outcomes. Still, the person-to-person relationship naturally promotes therapeutic encounters and responsibility in nursing and health care. Furthermore, Joyce Travelbee's reference is indicated as an anchor for home visits, as is the signalization of the importance of nursing theories being guaranteed in professional training, with opportunities for these professionals to be exposed to ways of understanding the metaparadigms of nursing. In any case, the care of the visiting nurses based on the person-to-person relationship in this study is seen as a care practice that has the potential to reconstruct the organizational scenario of interactions in the health field, especially in the experience of women who experience high-risk prenatal care. This is because the person-to-person theory has the potential to serve as a conceptual and practical model, subsidizing new care productions, valuing care centered on the person and the family, with the potential to accommodate the needs revealed in the meetings.
Person-to-person relationship in high-risk prenatal care: a case study
Keywords: Cuidado Pré-natal; Gravidez de Alto Risco; Visita domiciliar; Enfermeiras; Relações Interpessoais; Estudo de caso; Prenatal Care; High-Risk Pregnancy; House Calls; Nurses; Interpersonal Relation; Case study; CIENCIAS DA SAUDE::ENFERMAGEM